Investigation of the pitch accent of declarative statements of the kazakh language (on the basis of Praat programme) (Eurasian Journal of Philology Science and Education, 2016)
In this article the pitch accent of spontaneous statements in the Kazakh language is considered. Here the phonetic analysis which is carried out on the rate of the main tone in intonational contours of statements is described. For research of intonation of the Kazakh language the computer programs such as Praat, Doing Phonetics by Computer for development and analysis of speech signals were for the first time used. Using the Praat program, the spontaneous narrative statements in the Kazakh language of the speakers the volume of an interval of pitch accent of the narrative sentences and the main types of tone in this pitch accent were determined. This program can be used to research the sound system of any language at the segment and supersegment level.
Keywords: pitch accent; intonation; computer programmes; state¬ment; phonetic analysis